Perfil epidemiológico e fatores associados ao óbito por tuberculose no Departamento Regional de Saúde III do estado de São Paulo (2006-2008) - Yamamura, Mellina (2010)
The area of the Regional Department of Health (DRS) III has been demonstrating that it possesses good indicators of life quality, besides a number of establishments of health that you/they overcome the average of the state. However, studies demonstrate that the reality of control of TB is far away from the established rates for the organs of health. The death for TB should be a rare event, some authorities of health have been recommending the establishment of a surveillance that qualifies the information through the verification of the death, using methods that identify diagnosis mistakes, what really appears not just for the characteristics of the lethality as a quality indicator and of the treatment opportunity, but it goes much beyond, with the observation of deaths non included previously. It was aimed at to characterize the epidemic profile of the cases of TB that you/they developed for death registered in DRS III of the state of São Paulo, in the period from 2006 to 2008. It was treated of a quantitative and descriptive exploratory study, in which the information of the database were used TBWeb and YES. In the YES, it was used CID regarding the definition of TB, that you/they are the classifications of A15.0 to A19.9. After the individual collection of each bank, the information were confronted for the possible identification of cases subnotificados or sub detected. The characterization of the profile epidemic of the cases of TBWeb identified that, of the 640 cases notified in the period, 22 developed for death, being these 82% of the masculine sex; the predominant age group was of 30-59 years, but with occurrences also among the ends of age, only that in smaller frequency; education from 4 to 7 years of studies; defined occupation as others e not specified in the system; it forms lung clinic in 95% of the cases; in discovery type, 45% happened in the service of Emergency, and the comorbidade alcoholism appeared in 45% of the cases. In the YES, they were identified 34 death declarations that contained as basic cause one of CID with definition of TB and similar occurrence was observed: the masculine sex presents larger acometimento (73,5%), with age group between 30 and 59 years and 91% of the deaths for TB happened in the hospitalar. In the confrontment of the data, he/she identified only 22 cases in common, and 11 were notified in TBWeb, but they were not in the YES and 12 were in the YES, but they consisted in TBWeb. This way, the total of deaths for TB of the area was of 45 cases. The analysis of the systems of information YES and TBWeb identified inconsistency of data pointing flaws in the completion of the same ones. The information disponibilizeds indicate the need of better qualification of the same ones, what can feel through the involved professionals' larger training, as well as for the establishment of periodic confrontments of data in search of possible mistakes. Although they are clear the limitations of the research, imposed partially by the quality of the data, the study made possible to know the profile of the population more reached by the disease and your possible tendencies. It is done necessary also to detach that these information cannot be considered in real time, because although the systems are on-line, it is observed that there is still delay in the flow of the information.